1992
DOI: 10.1080/15235882.1992.10162636
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strategy Instruction on Bilingual Students' Cognitive Strategy Use in Reading

Abstract: There has been a great deal of emphasis on the teaching of thinking skills. For many second language learners. however, instruction in the use of cognitive strategy is almost nonexistent. Research identifying cognitive reading strategies used by second language learners has revealed a variety of strategies that students use to comprehend text. The identification of cognitive reading strategies has contributed to the development of instructional programs which teach students to use these strategies.The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
10
1
1
Order By: Relevance
“…Also, Hispanic students who were taught how to use text-related questioning, reported using the strategy more frequently than students who did not receive the training (Padron, 1992) and became more metacognitive about the benefits of questioning for comprehension (Jimenez, 1997;Padron, 1992). These results did not, however, specify whether students had benefited from certain question types (e.g., inferential questions) more than from others or whether student awareness of question types had any impact on their reading comprehension.…”
Section: English Language Learners and The Use Of Questioning As A Recontrasting
confidence: 45%
“…Also, Hispanic students who were taught how to use text-related questioning, reported using the strategy more frequently than students who did not receive the training (Padron, 1992) and became more metacognitive about the benefits of questioning for comprehension (Jimenez, 1997;Padron, 1992). These results did not, however, specify whether students had benefited from certain question types (e.g., inferential questions) more than from others or whether student awareness of question types had any impact on their reading comprehension.…”
Section: English Language Learners and The Use Of Questioning As A Recontrasting
confidence: 45%
“…While this study looked at more global outcomes, the results reflected the findings of previous work with younger students (Padrón, 1992) that suggest the potential benefits of cognitive strategy instruction for ELLs.…”
Section: Instruction To Enhance Reading Comprehensionmentioning
confidence: 47%
“…The students are instructed in four specific comprehension monitoring strategies: (a) summarizing, (b) self-questioning, (c) clarifying, and (d) predicting. Studies using reciprocal teaching have found that these strategies can successfully be taught to low-achieving students and that the use of these strategies increases reading achievement (Palinscar & Brown, 1984;Padron, 1985Padron, ,1992Padron, ,1993Pressley & Harris, 1990).…”
Section: Cognitively Guided Instructionmentioning
confidence: 97%